PSYCHOLOGICAL FEATURES OF DETERMINING SELF-CONFIDENCE IN STUDENTS - Yuldasheva M. E. PhD; Melkozieva M. A. (Journals Park Publishing, 2024)
The article describes the psychological features of determining the self-confidence of schoolchildren. The article also analyzes the ideas of schoolchildren to develop their self-confidence.
Keywords: student, self-confidence, development of self-confidence, nurturing self-confidence.